Anemia among Apparently Healthy Senegalese Children Aged 9-15 Months - Diouf, Saliou; Sylla, Assane; Diop, Fallou; Diallo, Abdallah; Sarr, Mamadou (International Journal of Child Health and Nutrition, 2013)
In Senegal, despite its high frequency, there is no real program to fight against anemia among infants. This work was carried out in the Dakar suburb from 1st September, 2009 to 27th January, 2010 among apparently healthy children aged 9-15 months at the time of their immunization against yellow fever and measles. They showed no known chronic condition or acute infection at the time of the survey. The objectives were to study the diet, prevalence, type and risk factors of anemia. The questionnaire was about whether the father and the mother were working and about the children’s diet during the first six months of their life. All the children underwent anthropometric measurements (weight and height) and a complete blood count. We considered children as anemic if the hemoglobin rate was below 11g/dl. Of the 245 children, 212 were anemic, which was a prevalence of 86.5%. This anemia, frequently of the microcytic hypochromic type (68. 86%) was significantly (p < 0.0003) observed among the children of housewives compared with those whose mothers were employed. Among anemic children, 60.8% were only taking breast milk with or without cereal porridge as a food supplement. The absence of consumption of protein, vegetables, fruits and dairy products was a risk factor for the occurrence of anemia (p <0.0001). In total, at the time immunization is stopped, almost all Senegalese children, while apparently healthy, still face nutritional anemia. The adverse consequences of anemia on child health require the implementation in developing countries of a specific program of struggle against anemia. The activity of vaccination might be the best opportunity to provide the nutritional education these mothers need.